2005
DOI: 10.1261/rna.7201805
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of RRF and EF-G from E. coli and T. thermophilus with ribosomes from both origins—insight into the mechanism of the ribosome recycling step

Abstract: Ribosome recycling factor (RRF), elongation factor-G (EF-G), and ribosomes from Thermus thermophilus (tt-) and Escherichia coli (ec-) were used to study the disassembly mechanism of post-termination ribosomal complexes by these factors. With tt-RRF, ec-EF-G can release bound-tRNA from ec-model post-termination complexes. However, tt-RRF is not released by ec-EF-G from ec-ribosomes. This complex with tt-RRF and ec-ribosomes after the tRNA release by ec-EF-G is regarded as an intermediate of the disassembly reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 52 publications
1
34
1
Order By: Relevance
“…In the first step, deacylated tRNA is released from the complex A by RRF and EF-G (Hirashima and Kaji 1973;Hirokawa et al 2002), resulting in the intermediate complex, complex B. Recent experiments suggested that RRF moves to the second site on the ribosome during this process from A to B in a fashion analogous to that of tRNA movement during the translocation step (Hirokawa et al 2002;Kiel et al 2003;Raj et al 2005). The next step is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first step, deacylated tRNA is released from the complex A by RRF and EF-G (Hirashima and Kaji 1973;Hirokawa et al 2002), resulting in the intermediate complex, complex B. Recent experiments suggested that RRF moves to the second site on the ribosome during this process from A to B in a fashion analogous to that of tRNA movement during the translocation step (Hirokawa et al 2002;Kiel et al 2003;Raj et al 2005). The next step is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, two RRF molecules (one for A through B to C and the other for C to C 0 ) would be required for the recycling of one ribosome, because the release of the initially bound RRF from the ribosome is necessary to release mRNA (Raj et al 2005). The dissociation of 70S ribosomes into subunits and the release of ribosomes from mRNA by RRF and EF-G measured by SDGC appear to share the same mechanism, as suggested by their equal sensitivity to the EF-G inhibitors (Table 4; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the splitting of the 70S ribosome, three laboratories support this reaction [16, 17 and 18]. Evidence for the order of the first two steps comes from the fact that the intermediate complex (mRNA-70S ribosome complex without tRNA) can be isolated in the presence of low concentrations of inhibitor [21] or with the use of Thermus thermophilus RRF [38]. However, this does not preclude the possibility that the first two steps might occur simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that Thermus thermophilus RRF, which does not function in Escherichia coli in vivo [36], can complement the defective E. coli RRF if a plasmid expressing IF3 is present [37]. Because T. thermophilus RRF, together with E. coli EF-G and ribosomes, functions only to release tRNA [38], an excess of IF3 might disassemble the 70S ribosomes left on mRNA without tRNA. These data suggest the possibility that excess IF3 might participate actively in the splitting of 70S ribosomes in vivo.…”
Section: Dissociation Of Ribosomes Into Subunits By Rrf and Ef-gmentioning
confidence: 99%